(untitled) (Al-Qamar, 2021)
The lexical method means a method in which the wording is discussed, and the lexical method in which the grammatical and syntactic discussion of the Quranic words will be discussed, as there is a book of Imam Ragheb Al-Isfahani with the name of Mufradat-ul-Quran and there are many books on Gharib-ul-Quran and also many books have been compiled with the name of Dictionaries of Quran. In the light of the introduction and style of the books, an attempt has been made to make it clear that understanding the literal method of understanding the Quran is very important, and it helps a lot in understanding the Quran.